The Effectiveness of the Communicative Approach on Improving Oral Expression Skills - Al-Hawamdeh, Mohammad; Ahmad Sawalha, Ahmad (Jordan Journal of Educational Sciences, 2018)
This study aimed at identifying the effectiveness of the communicative approach on improving oral expression skills among tenth grade students. The study was conducted on two sections of tenth grade students at Khaled bin Al-Walid high school at Irbid First Directorate of Education; totaling for (70) students assigned into two groups: experimental and control. In order to achieve the study goals, an observation tool of oral expression, consisting of (20) items, was developed. The tool covered four skills: intellectual, linguistic, vocal and gestural. The study employed pre – post test design, and revealed that teaching with communicative approach was effective in improving oral expression skills both individually and collectively among the experimental group, which was taught by this method, as compared with controls. The present study recommended placing more emphasis on the communicative approach, which plays an effective role in improving students’ oral expression skills, as well as encouraging Arabic language teachers to use this approach